2010
DOI: 10.1038/sj.bjc.6605712
|View full text |Cite
|
Sign up to set email alerts
|

Absence of the MGMT protein as well as methylation of the MGMT promoter predict the sensitivity for temozolomide

Abstract: Background:The DNA repair protein O6-methylguanine-DNA methyltransferase (MGMT) can cause resistance to the alkylating drug temozolomide (TMZ). The purpose of this study was to determine the relationship between the MGMT status, determined by means of several techniques and methods, and the cytotoxic response to TMZ in 11 glioblastoma multiforme (GBM) cell lines and 5 human tumour cell lines of other origins.Methods:Cell survival was analysed by clonogenic assay. The MGMT protein levels were assessed by wester… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
75
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(84 citation statements)
references
References 27 publications
3
75
0
3
Order By: Relevance
“…The presence of MGMT in tumoral glial cells has been shown to be responsible, at least in part, of TMZ resistance. 7,8,55 This is comforted by the association that we observe, between MGMT expression level and TMZ-growth inhibitory activity in both tumoral cell lines and GBM primary cultures. However, published data indicate that this correlation is far from being total, arguing for the involvement of Thus, besides their involvement in tumor development and progression, a number of miRNAs have been shown to influence cell responsiveness to chemotherapies.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…The presence of MGMT in tumoral glial cells has been shown to be responsible, at least in part, of TMZ resistance. 7,8,55 This is comforted by the association that we observe, between MGMT expression level and TMZ-growth inhibitory activity in both tumoral cell lines and GBM primary cultures. However, published data indicate that this correlation is far from being total, arguing for the involvement of Thus, besides their involvement in tumor development and progression, a number of miRNAs have been shown to influence cell responsiveness to chemotherapies.…”
Section: Discussionmentioning
confidence: 66%
“…[4][5][6] Resistance of GBMs to TMZ is reported to be mainly, but not exclusively, dependent on high levels of the DNA repair enzyme, O 6 -methylguanine methyltransferase (MGMT), which can reverse the methylation damage induced by alkylating agents. [7][8][9] Although a number of studies have shown that a deficiency of MGMT can augment the sensitivity of GBMs to alkylating agents such as TMZ, a panel of tumors with low levels of MGMT are nevertheless chemoresistant. 10,11 This suggests that additional mechanisms are involved in tumor resistance to 12 Thus, resistance of GBM cells to TMZ includes various events, such as loss of the phosphatase and tensin homolog (PTEN), leading to the activation of the phosphoinositide-3-kinase (PI3K)/Akt pathway, deficiency in the DNA mismatch repair system, mutations in the pro-apoptotic p53 protein, overexpression of the anti-apoptotic protein Bcl-2, or the selection of less-differentiated pre-existing resistant cells in the parental tumor.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, MGMT restores the methylated guanine and, finally, prevents the cells from the harmful alkylating groups [29]. Because of this function of MGMT, tumor cells develop drug resistance to chemotherapy [30,31]. MGMT is unique among DNA repair proteins because only one step is required for MGMT to transfer the alkyl group from O 6 -alkyl guanine (AG) to the active site of its own cysteine residue for restoring the methylated guanine through the direct reversal pathway [29][30][31].…”
Section: Discussionmentioning
confidence: 99%
“…These three cell lines contain a MGMT promoter region that is for the most part, methylated and do not express the MGMT protein (10,84,85).…”
Section: Temozolomidementioning
confidence: 99%